Aksesibilitas Rekam Medis Pasien Covid-19 Pada Rumah Sakit Pemerintah Dalam Perspektif Kearsipan: Array - 1 (Arsip Nasional Republik Indonesia, 2021)
A pre-government hospital is a government-owned health service institution that provides complete individual health services. When Indonesia was affected by the Covid-19 pandemic, the Covid-19 referral government hospital (Covid-19 RGH) became the foremost institution in treating patients who were victims of Covid-19. The ineffective implementation of government policies in preventing the spread of Covid-19 and the low level of public compliance have resulted in the number of Covid-19 cases continuing to increase and the number of victims requiring hospital treatment has also increased. This condition has an impact on the increasing number of medical records of Covid-19 patients (Covid-19 PMR) that must be managed by the Covid-19 RGH. In the midst of public concern about the Covid-19 pandemic, there is also concern over the potential misuse of the Covid-19 PMR as data/privacy information for hospital patients. This research on the Accessibility of the Covid-19 PMR at Government Hospitals in Archival Perspective aims to examine the accessibility of the Covid-19 PMR as a confidentialrecords. This study uses a qualitative approach with data collection methods sourced from the literature (document research). The results of the study show that there is a relationship between the security classification system and records access as a guide to records access with the protection of the Covid-19 RMP at the Covid-19 RGH.